Pembaharuan Peta Administrasi dan Peta Sarana Prasarana Desa Inotu Mewao Kecamatan Poli Polia Kolaka Timur - Lasitiha, Hasmirawati Injar (Yayasan Daarul Huda Kruengmane, 2026)
The creation of an administrative map for Inotu Mewao Village is part of the Community Service Program (KKN) program at Lakidende University in Poli-Polia District, East Kolaka Regency. This activity aims to assist the village government in providing accurate and up-to-date spatial data as a basis for regional development planning. The village administrative map serves as a visual aid showing boundaries, hamlets, road networks, rivers, and the location of public facilities in the village. The implementation method included data collection, field surveys using GPS, map digitization using QGIS, and validation of the results with village officials. The map creation process integrated primary data from the survey with secondary data from official sources such as the National Land Agency (BPN) and the district government. The results of the activity indicate that a digital and printed administrative map of Inotu Mewao Village has been created, containing information on boundaries, transportation networks, and the distribution of public facilities